1974
DOI: 10.1139/z74-179
|View full text |Cite
|
Sign up to set email alerts
|

Settlement patterns, territory size, and breeding density in the song sparrow (Melospiza melodia)

Abstract: In this study we investigated one possible proximate factor underlying year-to-year changes in mean territory size in song sparrows. We tested the hypothesis that birds defend smaller territories if they settle more or less at the same time, than if they settle on territories asynchronously. This idea is supported by some anecdotal field evidence in birds. To carry out the test, we did two types of removal experiments: (a) removing all the territory holders in an area at the same time and (b) removing territor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 0 publications
0
46
0
1
Order By: Relevance
“…Once the territory pattern is established, change may only be possible through the vacation of adjacent territories, which would then allow replacements to repack territories within the newly created space (Knapton and Krebs 1974). Such a scenario is less likely in species with a low adult mortality since the likelihood that adjacent territories are simultaneously vacated will be lower (Knapton and Krebs 1974).…”
Section: The Echo Of Settlementmentioning
confidence: 99%
“…Once the territory pattern is established, change may only be possible through the vacation of adjacent territories, which would then allow replacements to repack territories within the newly created space (Knapton and Krebs 1974). Such a scenario is less likely in species with a low adult mortality since the likelihood that adjacent territories are simultaneously vacated will be lower (Knapton and Krebs 1974).…”
Section: The Echo Of Settlementmentioning
confidence: 99%
“…Some studies have shown that floaters were drawn from among the most dominant individuals in the non-territorial fraction of the population (Knapton and Krebs, 1974;Smith and Arcese, 1989). In several studies in which removed territory owners were held captive and later released, such birds mostly managed to displace their replacements to regain their territories and mates, either in the same year or the next (Watson and Jenkins, 1968;Harris, 1970;Smith, 1978;Szuba and Bendell, 1988;Village, 1990).…”
Section: Are Floaters Phenotypically Different From Residents?mentioning
confidence: 99%
“…Even if adult males were deceived by the "female-like" plumage of SY males, serious fights should ensue as soon as the young males begin to sing-escalated fights often occur when two males view themselves as residents (Krebs, 1982). Since there is considerable evidence that young male passerines are subordinate to older males (Knapton and Krebs, 1974;Rohwer, 1975), they almost certainly have a lower resource-holding potential. It is unlikely that an SY male would be able to win such a contest against a more experienced adult, and an SY male may risk serious injury in an escalated fight.…”
Section: Female Mimicry Hypothesis (Fmh)mentioning
confidence: 99%